220k views
4 votes
This is the problem. I was out sick when we learned it and I have no idea what’s happening.

This is the problem. I was out sick when we learned it and I have no idea what’s happening-example-1
This is the problem. I was out sick when we learned it and I have no idea what’s happening-example-1
This is the problem. I was out sick when we learned it and I have no idea what’s happening-example-2
User Magdalina
by
5.6k points

1 Answer

4 votes

It is given that:


f(x)=6^x-4x;g(x)=(1)/(2)x+10

So the value of f(2)-g(-2) is given by substituting x=2 in f(x) and x=-2 in g(x) as shown below;


\begin{gathered} 6^2-4(2)-\lbrack(1)/(2)(-2)+10\rbrack=36-8-\lbrack-1+10\rbrack \\ =28-9 \\ =19 \end{gathered}

So the value is 19.

User Artem Loginov
by
5.4k points